Odpowiedź:
proszę:)
Szczegółowe wyjaśnienie:
b [2 (x+1)-3]/4=x/5/*20
5*[2 (x+1)-3]=4x
10x-5=4x/-4x
6x=5
x=5/6
c 8-x/2+5+x/4=12*(1-x/48)/*4
2*8-x/2+5+x=48*(1-x)/48
16-2x+5+x=48-x
21-x=48-x/+x
21≠48, więc równanie sprzeczne
d x+4/2-5==-3/*2
x+4-10=-6
x=-6+10-4
x=0
e 3x+2/4+5=2x+1/3/*12
9x+6+60=8x+4
9x+66=8x+4/-8x
x=-66+4
x=-62
f) x+2/4+1=x+6/4/*4
x+2+4=x+6/-x
6=6 równanie tożsamościowe
g) x/3+2=7/:8
x+6=21
x=21-6
x=15
h) (4-x+2)/7=(8x-3+2x)/-10/*70 (tu wspólny mianownik, mnożymy każdy mianownik i licznik do wspólnego mianownika)
40-10x+20=-56x+21-14x
60x+60=21
x=21-60/60
x=-39/60=-13/20